In Vivo Knockout of the Vegfa Gene by Lentiviral Delivery of CRISPR/Cas9 in Mouse Retinal Pigment Epithelium Cells - Andreas Holmgaard; Anne Louise Askou; Josephine Natalia Esther Benckendorff; Emil Aagaard Thomsen; Yujia Cai; Toke Bek; Jacob Giehm Mikkelsen; Thomas J. Corydon (Elsevier, 2017)
Virus-based gene therapy by CRISPR/Cas9-mediated genome editing and knockout may provide a new option for treatment of inherited and acquired ocular diseases of the retina. In support of this notion, we show that Streptococcus pyogenes (Sp) Cas9, delivered by lentiviral vectors (LVs), can be used in vivo to selectively ablate the vascular endothelial growth factor A (Vegfa) gene in mice. By generating LVs encoding SpCas9 targeted to Vegfa, and in parallel the fluorescent eGFP marker protein, we demonstrate robust knockout of Vegfa that leads to a significant reduction of VEGFA protein in transduced cells. Three of the designed single-guide RNAs (sgRNAs) induce in vitro indel formation at high frequencies (44%-93%). A single unilateral subretinal injection facilitates RPE-specific localization of the vector and disruption of Vegfa in isolated eGFP+ RPE cells obtained from mice five weeks after LV administration. Notably, sgRNA delivery results in the disruption of Vegfa with an in vivo indel formation efficacy of up to 84%. Sequencing of Vegfa-specific amplicons reveals formation of indels, including 4-bp deletions and 2-bp insertions. Taken together, our data demonstrate the capacity of lentivirus-delivered SpCas9 and sgRNAs as a developing therapeutic path in the treatment of ocular diseases, including age-related macular degeneration.